THE NEED TO IMPROVE RECONSTRUCTIVE PLASTIC SURGERY IN CHILDREN WITH TOTAL AND SUBTOTAL EPISPADIUS - Xayrulla X.Xudaynazarov; Tojiddin S. Fayzullaev; Xojiakbar S. Usmanov; Jasur A.Allanazarov (Scholar Express Journals, 2023)
To date, 11.3% of newborns are born with various developmental anomalies, and more than 40% of them are due to disorders and anomalies of the genitourinary system (1,3,5, etc.). the norm, complicated by urinary incontinence, is 8.0%. Comprehensive treatment of bladder malformations complicated by urinary incontinence in children has long attracted the attention of practicing surgeons and is still on the agenda as one of the most urgent problems of pediatric surgery (2,5, etc.). In particular, the results of surgical treatment of cases of total and subtotal epispadias in combination with bladder exstrophy are unsatisfactory. According to the leading specialists of Russian clinics, including N. E. Savchenko and V. M. Derzhavin, in 1978, complete and complete urinary retention after sphincteroplasty performed according to V. M. Derzhavin, in cases of contacting the clinic with total and subtotal epispadias in 45% of cases and 28-32% of cases of partial seizures. Statistics show that 2 out of 10 patients who underwent sphincteroplasty according to V. M. Derzhavin had no benefit at all, and 1 out of 10 had only a partial goal. Extensive studies conducted in our republic on these operations have shown that there are good and satisfactory results of these operations - only 60.0% All these indicators still have their problems in this regard, shows that she has not found a solution.
Keywords: Total; subtotal epispadias; endovisual surgery; sphincteroplasty